Internalization of Religious Moderation Values through Islamic Religious Education Learning - Imam Jafar (International Journal of Islamic Education Studies, 2025)
This study explores the internalization of religious moderation values through Islamic Religious Education (PAI) at MTs Al-Yakin Pungpungan. The research is motivated by the urgent need to strengthen tolerance, balance, and inclusivity among students in facing religious diversity and socio-cultural plurality. Employing a qualitative approach with interviews, observations, and documentation, the study aims to understand how moderation values are conveyed, practiced, and sustained in the school environment.The findings reveal that teachers play a central role not only as educators but also as role models who demonstrate moderate attitudes in daily interactions. The school culture, including routine activities, policies, and symbolic practices, reinforces these values systematically. Furthermore, collaboration with families and communities strengthens the continuity of moderation practices beyond the classroom setting. Despite challenges such as family diversity, digital media influences, and limited resources, adaptive strategies have been implemented, including curriculum integration, experiential learning, parental involvement, and digital literacy awareness. The study concludes that the internalization of religious moderation in Islamic Religious Education is a dynamic and continuous process that requires synergy among teachers, schools, families, and communities. This research contributes to the academic discourse by highlighting practical models of moderation education in Islamic schools and emphasizes the importance of holistic, contextual, and participatory approaches in shaping students who are tolerant, balanced, and morally responsible in a plural society.